Dynamic Fluid Module: Problem-Based Learning Combined with STEM to Increase Students' Scientific Creativity - Suyidno Suyidno; Raisa Hadianti; Sarah Miriam; Joko Siswanto (Jurnal Penelitian Pendidikan IPA, 2024)
Scientific creativity is one of the main competencies in 21st century life, but this competency is not practiced in schools. This study aims to describe the effectiveness of dynamic fluid module using STEM-PBL to improve students' scientific creativity. This module contains lesson plans, module content, materials and scientific creativity tests. This research includes research and development using an adaptation of the ADDIE model. The research trial used a one group pretest and posttest design on 21 students of class XI IPA 1 SMA Negeri 1 Takisung. Data were obtained from student learning outcomes tests, with module effectiveness of 0.41 in the moderate category. Thus, the dynamic fluid module using STEM-PBL developed is effective for increasing students' scientific creativity.